Cu2O/CuO Electrocatalyst for Electrochemical Reduction of Carbon Dioxide to Methanol. Issue 3 (10th November 2020) - Roy, Animesh; Jadhav, Harsharaj S.; Gil Seo, Jeong
Abstract: Herein, we report the controlled and direct fabrication of Cu2 O/CuO thin film on the conductive nickel foam using electrodeposition route for the electrochemical reduction of carbon dioxide (CO2 ) to methanol. The electrocatalytic reduction was performed in CO2 saturated aqueous solution consisting of KHCO3, pyridine and HCl at room temperature. CO2 reduction was carried out at a constant potential of −1.3 V for 120 min to study the electrochemical performance of the prepared electrocatalysts. Cu2 O/CuO shows better electrocatalytic activity with highest current density of 46 mA/cm 2 . The prepared catalyst can be an efficient and selective electrode for the production of methanol. Abstract :